Concentration and Distribution of Oligochaeta Worms in the Waters of Kejapanan, Pasuruan, Indonesia Polluted by Mercury Waste using DNA Barcode - Irawati Mei Widiastuti; Moh. Awaludin Adam; Ernawati (Jurnal Ilmiah Perikanan dan Kelautan, 2025)
Graphical Abstract Higlight Research Based on AAS test, results showed that the St2 sample has the highest concentration of mercury compared to other locations. St2 samples are samples taken right at the pollutant source. The results showed that the samples consist of the Nadidae family with two species, namely Limnodrilus hoffmeisteri and Branchiura sowerbyi. The COI gene that was successfully amplified had a length of approximately 700 bp using a 3000 bp DNA ladder as a comparison. Based on the results of the SEM-EDX test, the worm samples contained several elements. The majority of them are organic except Al, Si, and Ti. Aluminium (Al), Silicon (Si), and Titanium (Ti) are metals that are used by organisms.     Abstract Physiological monitoring of mercury waste contamination can be carried out using the biota around the waters. This study aims to identify concentration of Hg and the types of worms in the waters of Kejapanan, Pasuruan, East Java with a molecular approach. Target gene amplification was carried out using the mitochondrial genome COI barcode primer. Analysis of molecular identification was performed with DNA analysis and phylogenetic, similarity, DNA sequence variation, genetic distance, and the BOLD System. The concentration Hg was analyzed using AAS and the distribution of mercury in the worms was analyzed using SEM Edax Mapping. The results showed that the pollutant source area (St2 sample) has the highest concentration of mercury compared to other locations. The results of molecular identification indicate the formation of two clusters. The amplified samples produced DNA bands according to the target (600-700 bp), and the process was continued with morphological-based-key identification. The results showed that they consist of the family Nadidae with two species, namely Limnodrilus hoffmeisteri and Branchiura sowerbyi. A DNA length of 709 bp as well as nucleotide composition. BLAST results showed that species L. hoffmeisteri and B. sowerbyi had similarity indexes of 99% and 86%, respectively. Based on the research results, it was found that there was an accumulation of mercury exposure in worms in polluted areas. For this reason, the results of this study can provide a novelty that worms can be used as biomonitoring of water pollution using the barcode data.